Differences of blood glucose and insulin in childbearing aged women acceptors of depo medroxy progesterone acetat with non acceptors in Padang City 2017 - Sari, Sri Rahma; Reza, Mohamad; Arisanty, Dessy; Lipoeto, Nur Indrawaty (International Journal of Research in Medical Sciences, 2019)
Background: Contraception was the way to prevent pregnancy, both temporarily and permanently. Depot Medroxyprogesterone Acetate (DMPA) is a contraceptive injection of synthetic progesterone hormone and is injected every three months, which is most commonly used currently, but that emerging consequences of long time usage of contraception, especially the hormonal one, cannot be denied. This research was aimed to see difference in blood sugar, insulin and lipid profile in childbearing aged women who used DMPA injection and Non-Acceptors. Methods: The study was observational with the comparative cross sectional approach. Research was conducted in the Biomedical Laboratory in Andalas University and Regional Technical Service Unit (UPTD) Laboratory in West Sumatera Province. Data was taken from December 2017 until June 2018. The research sampled 48 DMPA acceptors and 48 non-Acceptors. Sampling technique used stratified random sampling. Examination of blood glucose was carried out by the enzymatic method of GOD-PAP, ELISA for insulin. Data were analyzed using independent T-test and if the data was not normal, non parametric Mann-Whitney test was used. The differences were considered statistically significant if the value of p<0.05. Results: The mean blood glucose acceptors 91.27mg/dl, non acceptors 88.83mg/dl and mean Insulin acceptors 23.63mIU/L, non akseptor 24.63mIU/L. The results showed that there were no significant differences between DMPA acceptors and non acceptors (p>0.05) in blood glucose (0.059) and insulin (p = 0.603). Conclusions: There were no significant differences in blood glucose and insulin levels between DMPA acceptors and non acceptors.